Limits of ZnO Electrodeposition in Mesoporous Tin Doped Indium Oxide Films in View of Application in Dye-Sensitized Solar Cells - Dunkel, Christian (Materials (Basel), 2014)
Well-ordered 3D mesoporous indium tin oxide (ITO) films obtained by a templated sol-gel route are discussed as conductive porous current collectors. This paper explores the use of such films modified by electrochemical deposition of zinc oxide (ZnO) on the pore walls to improve the electron transport in dye-sensitized solar cells (DSSCs). Mesoporous ITO film were dip-coated with pore sizes of 20–25 nm and 40–45 nm employing novel poly(isobutylene)-b-poly(ethylene oxide) block copolymers as structure-directors. After electrochemical deposition of ZnO and sensitization with the indoline dye D149 the films were tested as photoanodes in DSSCs. Short ZnO deposition times led to strong back reaction of photogenerated electrons from non-covered ITO to the electrolyte. ITO films with larger pores enabled longer ZnO deposition times before pore blocking occurred, resulting in higher efficiencies, which could be further increased by using thicker ITO films consisting of five layers, but were still lower compared to nanoporous ZnO films electrodeposited on flat ITO. The major factors that currently limit the application are the still low thickness of the mesoporous ITO films, too small pore sizes and non-ideal geometries that do not allow obtaining full coverage of the ITO surface with ZnO before pore blocking occurs.